2021
DOI: 10.1111/jocs.15729
|View full text |Cite
|
Sign up to set email alerts
|

Combination plate and band fixation for primary closure in bilateral lung transplantation

Abstract: Background Sternal complications are common following transverse thoracosternotomy in patients undergoing bilateral lung transplantation. We present a single‐institution experience using a next generation rigid fixation system for primary sternal closure following transverse sternotomy for bilateral lung transplantation. Methods Retrospective review was performed on all patients who had bilateral sequential lung transplants utilizing a transverse thoracosternotomy from 2016 to 2020. Demographics, baseline char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although plate fixation is generally adequate for long bone fractures or mid-sternotomy, the plating technique is inappropriate as a sternal fixation method in patients with transverse sternotomy affected by excessive outward translation and paradoxical abdominal movement. Recently, Boudreaux, et al 10 reported that sternal complications in clamshell incision lung transplantation could be reduced by applying plate fixation as the primary sternal closure technique. Our experience shows that titanium plate fixation is similar to conventional sternal wiring fixation, such as the primary sternal fixation technique for transverse sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although plate fixation is generally adequate for long bone fractures or mid-sternotomy, the plating technique is inappropriate as a sternal fixation method in patients with transverse sternotomy affected by excessive outward translation and paradoxical abdominal movement. Recently, Boudreaux, et al 10 reported that sternal complications in clamshell incision lung transplantation could be reduced by applying plate fixation as the primary sternal closure technique. Our experience shows that titanium plate fixation is similar to conventional sternal wiring fixation, such as the primary sternal fixation technique for transverse sternotomy.…”
Section: Discussionmentioning
confidence: 99%